Shared mental models in handball and soccer elite teams - Giske, R.; Gjerde, J.; Gard, H. S.; Johansen, B. T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Shared mental model (SMM) is held as important facilitating team performance and it is considered a useful construct for analysing elite team practice. Canon-Bowers, Salas, & Converse (1993) describe SMM as knowledge structures held by members of a team that enable them to form accurate explanations and expectations for the task, and in turn, to coordinate their actions and adapt their behaviour to demands of the task and other team members. Giske, Rodahl & Høigaard (2015) argues that SMM is a useful construct for analysing elite team practice and coaching behaviour. The aim of this study is to explore how elite coaches in handball and soccer reflect on team cognitive properties and how these attributes are developed through team practice. In study 1 we investigated the reflections on shared mental models and coaching efforts to develop it in National handball teams. Three coaches participated. In study 2 we elaborate coaches` reflections and players` experience of how shared notions of game tasks is affected by practice in two elite soccer teams. Two UFFA-pro coaches from Norwegian Premier League, and four elite players volunteered to participate. A qualitative content analysis (Morgan, 1993) of the verbatim transcription was undertaken. The interviews in both studies revealed that measurements such as use of video, team meetings, and field practice were used in both ballgames to enhance a shared mental model. The national coaches in handball reported systematic practice with intention to promote coordination where repetitions of the coordinative patterns in typical game situation were emphasized. Distribution of tasks in game situations and timing seems to be vital pedagogical content elements contributing to establish shared situational awareness. Implicit communication is a characteristic of teams sharing a mental model and this seems to be especially prominent in handball coaches` reflections and proactive distinct bodily movements are emphasised as a crucial requirement for coordination. The soccer players` draws attention towards knowledge about team member attributes within more explicit task team generic guidelines.